The relationship of career development, training and compensation on employee performance in Northern Malaysia Life Insurance company - Mohd Hafez, Abas (2020)
The purpose of this research is to examine the relationship of career development, training and compensation on employee performance among insurance consultant at Malaysia life insurance company in Northern Malaysia comprise Perlis, Kedah and Penang. The population of this research is 2,244 insurance consultants in five major life insurance industries players in Malaysia and the sample size of this research is 335 respondents among insurance consultant. The research adopts quantitative research method and questionnaire form was utilized to collect the data from the target respondent. In this research, the analysis of the data is using the Statistical Package for the Social Sciences (SPSS). From Pearson correlation analysis, the results of this research are there are positive and significant relationship between the variables with the value of career development is 0.432, training is 0.583 and compensation is 0.538 From this result it can be concluded that training variable have the strongest significant relationship on employee performance in this research. The research theoretical implication this research will assist to an effective and better implementation for future researcher on the factors influencing employees’ performance. The practical implication of this research is that it can serve as a guide for organizations to introduce and update existing policies in line with developments in human resource management practices.